The Correlation Between Students’ Translation Ability and Their Reading Comprehension - Nurul Hastini; Andi Mega Januarti Putri; Nur Husnil Khatimah (GLENS: Global English Insights Journal, 2023)
The aim of this study was to examine the correlation between students' translation ability and their reading comprehension among eleventh-grade mathematics and science students at SMAN 1 Wonomulyo. This study used a quantitative approach, employing a correlational research design. The sample consisted of 36 students selected through a simple random sampling technique from a total population of 212 students. The study employed translation and reading tests as its primary instruments. The data analysis using SPSS indicated a two-tailed significance value of 0.069, which was greater than the standard 0.05 threshold. Additionally, the result obtained using the multiple correlation formula showed a value of 0.329 with 34 degrees of freedom. The correlation coefficient (r-value) was -0.306, which fell below the calculated threshold of 0.329. A t-test was conducted, yielding a t-value of 1.8741724, which was less than the critical t-table value (2.03224) with 34 degrees of freedom at a 0.05 level of significance. Based on the data analysis, the study concluded that the research hypothesis (Ha) suggesting a significant correlation between students' translation ability and reading comprehension was rejected, while the null hypothesis (H0) suggesting no significant correlation was accepted.